Seasonal changes effects on the serotonin and melatonin transmission - Abbas, Syed Atif; Khan, Umeed Ali; Helal Uddin, A.B.M. (Intellectual Consortium of Drug Discovery & Technology Development, 2011)
Neurotransmission of serotonin and its derivative is said to be effected by changing of season in temperate countries. The effect of photoperiod and temperature can alter the production of serotonin and melatonin in body. The depression in serotonin availability in brain leads to a depressive or bipolar disorder. The activity of tryptophan hydroxylase to synthesis serotonin and monoamine oxidase (MAO) to inactivate serotonin is affected by season change. Calcitriol can stimulate tryptophan hydroxylase to produce serotonin. CREM gene works by memorizing work base on previous memory on how much serotonin will be produce. Melatonin it’s a serotonin derivative act as endocrine because it produce from pineal gland and retina. Melatonin has diurnal circadian pattern. Melatonin production is not decline by increasing in age. Arylalkylamine N-acetyltransferase (AA-NAT) gene is one of the cAMP inducible genes is an enzyme important in production of melatonin. Key words: Serotonin, melotonin transmission, depression, calcitriol